2021
DOI: 10.3390/ijms22115667
|View full text |Cite
|
Sign up to set email alerts
|

Dual Actions of A2A and A3 Adenosine Receptor Ligand Prevents Obstruction-Induced Kidney Fibrosis in Mice

Abstract: Kidney fibrosis is the final outcome of chronic kidney disease (CKD). Adenosine plays a significant role in protection against cellular damage by activating four subtypes of adenosine receptors (ARs), A1AR, A2AAR, A2BAR, and A3AR. A2AAR agonists protect against inflammation, and A3AR antagonists effectively inhibit the formation of fibrosis. Here, we showed for the first time that LJ-4459, a newly synthesized dual-acting ligand that is an A2AAR agonist and an A3AR antagonist, prevents the progression of tubulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“… 29 , 58 It is reported that supplementation of high-fat obesogenic diets with cholic acid or chenodeoxycholic acid inhibits obesity development in mice. 55 Our results confirmed this point exactly.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 29 , 58 It is reported that supplementation of high-fat obesogenic diets with cholic acid or chenodeoxycholic acid inhibits obesity development in mice. 55 Our results confirmed this point exactly.…”
Section: Discussionsupporting
confidence: 84%
“… 6 , 37 , 54 Alterations in extracellular adenosine signaling can modulate immune responses, inflammatory processes and immunosuppression. 6 , 55 Adenosine activates four specific membrane adenosine receptors, which are named adenosine receptor A1 (A1AR), adenosine receptor A2A (A2AAR), adenosine receptor A2B (A2BAR), and adenosine receptor A3 (A3AR). These ARs belong to the family of G protein-coupled receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adenosine antagonist 8-(p-Sulophenyl) theophylline stopped this from happening ( 70 , 91 ). A detailed examination of A3 agonists and antagonists revealed that, although A3 receptors may contribute to the suppression of the oxidative burst, the inhibition is primarily mediated by A2a activation ( 92 , 93 ).…”
Section: Effects Of Adenosine On Immune Cellsmentioning
confidence: 99%
“…Since A 3 AR antagonists or A 2A AR agonists protect against DKD, it is reasonable to develop AR modulators with dual action as an A 3 AR antagonist and an A 2A AR agonist in order to have better protective effects against DKD. We showed for the first time that LJ4459, a newly synthesized dual-acting ligand, prevents the progression of tubulointerstitial fibrosis in obstructed kidneys [ 94 ]. It will be interesting to determine whether this dual-acting ligand has better therapeutic efficacy against DKD than an A 3 AR antagonist or an A 2A AR agonist.…”
Section: The Role Of Adenosine and Adenosine Receptors In The Kidneymentioning
confidence: 99%